2023
DOI: 10.1038/s43018-023-00600-4
|View full text |Cite
|
Sign up to set email alerts
|

CD8+ T cells maintain killing of MHC-I-negative tumor cells through the NKG2D–NKG2DL axis

Abstract: The accepted paradigm for both cellular and anti-tumor immunity relies upon tumor cell killing by CD8+ T cells recognizing cognate antigens presented in the context of target cell major histocompatibility complex (MHC) class I (MHC-I) molecules. Likewise, a classically described mechanism of tumor immune escape is tumor MHC-I downregulation. Here, we report that CD8+ T cells maintain the capacity to kill tumor cells that are entirely devoid of MHC-I expression. This capacity proves to be dependent instead on i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 56 publications
0
19
0
Order By: Relevance
“…These CD8 + T cells recognize OVA antigen. 35,36 We treated these CD8 + T cells using ATRA@CpG-NPs with or without OVA and detected the content of IL-2 and IFN-γ in the supernatants. Cells treated with ATRA@CpG-NPs + OVA secrete significantly higher amounts of IL-2 and IFN-γ compared to those treated with ATRA@CpG-NPs and PBS treatment, suggesting that ATRA@CpG-NPs + OVA could activate antigen-specific CD8 + T cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These CD8 + T cells recognize OVA antigen. 35,36 We treated these CD8 + T cells using ATRA@CpG-NPs with or without OVA and detected the content of IL-2 and IFN-γ in the supernatants. Cells treated with ATRA@CpG-NPs + OVA secrete significantly higher amounts of IL-2 and IFN-γ compared to those treated with ATRA@CpG-NPs and PBS treatment, suggesting that ATRA@CpG-NPs + OVA could activate antigen-specific CD8 + T cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Enrichment analysis demonstrated that patients in cluster 1 exhibited increased activation of cancer-related pathways, including hypoxia, glycolysis, and the p53 pathway. TIME is infiltrated by a variety of immune cells, among which CD8 + or cytotoxic T lymphocytes exert tumor-killing function, while regulatory T cells attenuate effector T cell activity and promote immunosuppression in TIME [ 28 , 29 ]. Different immune cell ratios could promote tumor growth and metastasis by shaping TIME and thus mediating the immune escape of tumor cells [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study we also observed a sharp increase in stromal expression of Nectin2 in BRCA2 mutated pancreatic cancer patients, with inhibitory effects on cytotoxic CD8+ T-cells 16 , raising the possibility of its use as a stromal biomarker in different cancers. Thus, the spatial organization and quantity of CAFs in tumors may dictate reduction of cytotoxic lymphocyte activity via the NKG2D-DNAM-1 axis, since both NK cells and CD8+ T-cells rely on these receptors for immune-surveillance 92,93 . On the other hand, the observation that CAFs upregulate NKG2D and DNAM-1 ligands also opens the possibility of utilizing activated NK cells to modulate solid tumors that are characterized by high desmoplasia as a combinatorial immunotherapeutic approach; One interesting avenue may incorporate adoptive NK cell administration followed by conventional checkpoint blockade that may initially reduce stromal content, and therefore provide potent synergistic effects in solid tumors.…”
Section: Discussionmentioning
confidence: 99%